1984
DOI: 10.1002/pssb.2221210254
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence of GaSe: Mn Single Crystals

Abstract: The luminescent properties of undoped and doped GaSe single crystals in the region of the fundamental absorption edge have been studied by a number of authors /1 to l o / . The impurity photoluminescence (PL) in GaSe is not completely understood as compared to the near-gap luminescence /11 to 13/. Investigations of P L spectra of GaSe:Mn single crystals at 4.2 K a r e dealt with by the authors of /12/ and /13/. However, the authors of these reports have not studied excitation spectra, P L kinetics, dependences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

1986
1986
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…However, the type of the conduction of the Mn-doped samples is p-type from Hall effect measurement. Tagiev et al have shown that in layered GaSe crystals the Mn ions occupy the Ga site and are in the bivalent state Mn 2+ [17]. We consider that the acceptor level in Mn-doped GaS is connected to Mn atoms at Ga site.…”
Section: Methodsmentioning
confidence: 97%
“…However, the type of the conduction of the Mn-doped samples is p-type from Hall effect measurement. Tagiev et al have shown that in layered GaSe crystals the Mn ions occupy the Ga site and are in the bivalent state Mn 2+ [17]. We consider that the acceptor level in Mn-doped GaS is connected to Mn atoms at Ga site.…”
Section: Methodsmentioning
confidence: 97%
“…In this issue, detailed information on doping processes plays an important role. The problem of doping, that was investigated early without drawing definitive conclusions, [8][9][10][11][12][13] has been recently approached by other groups that have specially studied the influence of impurities from groups I and II as acceptors in GaSe. [14][15][16][17][18][19][20][21] Room temperature hole concentrations of the order of 10 15 -10 16 cm Ϫ3 have been reported by doping with Cd, 17 Zn, 18 Cu, 19 and Ag.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] The possibility of preparing GaSe high-quality thin films through the so-called van der Waals epitaxy [9][10][11][12] has lead to a renewed interest because of the potential optoelectronic applications. The problem of doping, that was early investigated without drawing definitive conclusions, [13][14][15][16][17][18] has been recently attacked by other groups that have specially studied the role of group II impurities as acceptors in GaSe. [19][20][21][22][23] Attempts to get low resistivity n-type GaSe have been up to now unsuccessful.…”
Section: Introductionmentioning
confidence: 99%